Structural Transitions of the Metal-Organic Framework DUT-49(Cu) upon Physi- A nd Chemisorption Studied by in Situ Electron Paramagnetic Resonance Spectroscopy - Polyukhov, Daniil M.; Krause, Simon; Bon, Volodymyr; Poryvaev, Artem S.; Kaskel, Stefan; Fedin, Matvey (Journal of Physical Chemistry Letters, 2020)
Flexible metal-organic frameworks (MOFs) exhibit a variety of phenomena attractive for basic and applied science. DUT-49(Cu) is one of the remarkable representatives of such MOFs, where phase transitions are coupled to pressure amplification and "negative gas adsorption". In this work we report important insights into structural transitions of DUT-49(Cu) upon physi- A nd chemisorption of gases and volatile liquids obtained by in situ electron paramagnetic resonance (EPR) spectroscopy. In this method, phase transitions are detected via the zero-field splitting in dimeric copper(II) units. First, a new approach was validated upon physisorption of n-butane. Then, using diethyl ether, we for the first time demonstrated that chemisorption can also trigger phase transition in DUT-49(Cu). On the basis of the EPR results, the transition appears completely reversible. The developed EPR-based approach can also be extended to other flexible MOFs containing paramagnetic metal paddlewheels, where high sensitivity and spectral resolution allow in situ studies of stimuli-induced structural variability.
CRIS-Team Scopus Importer:2022-04-14